ЛІНГВОКОМУНІКАТИВНІ МЕХАНІЗМИ ФОРМУВАННЯ ІМІДЖУ ПРАВООХОРОННОЇ ОРГАНІЗАЦІЇ - Лисичкіна, Ірина Олексіївна (Studia Philologica, 2013)
The article highlights the communicative specificity of law-enforcement organizational image. The nature, communicative features and strategy of law-enforcement organizational image formation are identified on image videos of the Interior Troops of the Ministry of Internal Affairs of Ukraine, the US National Guard and Gendarmerie Nationale de la France. The communicative model of law-enforcement organizational image formation is suggested.